2010
DOI: 10.3148/71.3.2010.127
|View full text |Cite
|
Sign up to set email alerts
|

Food Purchasing and Food Insecurity: Among Low-income Families in Toronto

Abstract: Despite their resourcefulness, low-income families struggle to feed their families. Dietitians have an important role to play as advocates for adequate income supports to promote food security and nutritional health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
29
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
4
29
2
Order By: Relevance
“…This is in contrast with previous studies (8)(9)(10) which found that the purchase of recommended healthy foods declined with increasing food insecurity due to lack of money. This could be due to differences in the cost of these foods or the size of government allowances across the countries or cities in which these studies were conducted.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with previous studies (8)(9)(10) which found that the purchase of recommended healthy foods declined with increasing food insecurity due to lack of money. This could be due to differences in the cost of these foods or the size of government allowances across the countries or cities in which these studies were conducted.…”
Section: Discussioncontrasting
confidence: 99%
“…Levels of food insecurity due to lack of money have been shown to be as high as 11 % in the USA (5) , 5 % in Australia (6) and 8 % in the UK (7) . The evidence available suggests that food insecurity related to a lack of money is associated with a decline in total household food supplies and of nutritious foods such as dairy, meat, grains, fruit and vegetables (8)(9)(10) . A second indictor relates to physical limitations, such as the inability to carry groceries.…”
mentioning
confidence: 99%
“…[12][13][14][15][16]25 Consistent with our observation of less nutrition label use among adults in foodinsecure households, accounts of the priorities that food-insecure parents apply to their food purchasing decisions suggest that price and family food preferences take precedence over nutrition considerations when resources are scarce. 13,14,25 The discrepancy between our results and US program evaluation data showing that improving adults' food skills can reduce their food insecurity (see for example refs. [18][19][20] may simply reflect differences in the scope of these research endeavours.…”
Section: Discussionsupporting
confidence: 73%
“…Less is known about the importance of adults' food skills and self-provisioning activities in mitigating the effects of limited incomes on household food security, but community cooking and gardening programs and other educational initiatives aimed at strengthening individuals' basic food skills are widely perceived as valuable interventions to improve the food security of low-income households. [8][9][10][11][12] While the resourcefulness and frugality of adults tasked with food shopping in the context of limited resources have been well documented, [12][13][14][15][16] there has been little assessment of the relation between adults' food skills and household food security. The few Canadian studies of programs designed to strengthen the budgeting and cooking skills of at-risk adults suggest that these interventions have limited impact on food insecurity, 8,17 but more structured evaluations of broader-scale, targeted nutrition education initiatives in the US have shown reductions in household food insecurity with improved food shopping and cooking skills (see for example refs.…”
mentioning
confidence: 99%
“…The proportion of overall store sales from different product categories cannot be attributed to individual-or household-level characteristics. However, previous research with low-income families in Toronto has demonstrated the resourcefulness of those living under serious economic constraints manifested in household food insecurity, 25,26 and the wide array of factors contributing to decision making with household budgets. For example, among low-income families, while price is a key factor in purchasing decisions, and social assistance payments appear to structure monthly food purchases, economizing may depend on preference and health considerations, as well as perishability, durability and other value attributes associated with food items.…”
Section: Discussionmentioning
confidence: 99%